2005
DOI: 10.1016/j.femsec.2004.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Diel changes in bacteriochlorophyll a concentration suggest rapid bacterioplankton cycling in the Baltic Sea

Abstract: Aerobic anoxygenic phototrophs were recently found to constitute a significant portion of the marine microbial community. These bacteria use bacteriochlorophyll-containing reaction centers to perform photoheterotrophic metabolism. A new instrument for routine measurements of both chlorophyll a and bacteriochlorophyll a was used for monitoring anoxygenic phototrophs in the Baltic Sea in late summer 2003. Bacteriochlorophyll a concentration ranged from 8 to 50 ngl(-1), with an average bacteriochlorophyll/chlorop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Consequently, generalizing statements postulating a stringent inhibition of BChl synthesis in marine aerobic anoxygenic photosynthetic bacteria even by low light intensities [ e.g. 36], [37] have to be reconsidered. Interestingly, our data are in line with early results of Kolber et al [38] who found only a minor effect of light on pigment synthesis in aerobic bacteriochlorophyll-containing bacteria in marine ecosystems, but a diel growth cycle in oxygenic phototrophs with chlorophyll synthesis restricted to periods of darkness.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, generalizing statements postulating a stringent inhibition of BChl synthesis in marine aerobic anoxygenic photosynthetic bacteria even by low light intensities [ e.g. 36], [37] have to be reconsidered. Interestingly, our data are in line with early results of Kolber et al [38] who found only a minor effect of light on pigment synthesis in aerobic bacteriochlorophyll-containing bacteria in marine ecosystems, but a diel growth cycle in oxygenic phototrophs with chlorophyll synthesis restricted to periods of darkness.…”
Section: Resultsmentioning
confidence: 99%
“…where t is time, D is the decay rate, [BChl a] t is BChl a signal at time t, and [BChl a] start is the initial BChl a signal recorded in the morning (Koblížek et al 2005).…”
Section: Bacteriochlorophyll Turnover Measurementsmentioning
confidence: 99%
“…This pigment is found in aerobic anoxygenic phototrophic (AAP) bacteria (i.e., photoheterotrophic organisms), which represented 1-4% of the total bacteria in the studied regions (Koblížek 2015). Diel changes of this pigment were earlier proposed as a convenient way to determine the mortality of AAP bacteria (Koblížek et al 2005), which is related to the growth rate under steady-state conditions (Koblížek et al 2007). We conducted BChl a turnover rate measurements during BIOSOPE, OC443, and KM1013.…”
Section: Independent Corroboration Of Rapid Membrane Turnover Ratesmentioning
confidence: 99%
“…Bacteriochlorophyll a (BChl a) concentrations were measured on an FL3500-FT fluorometer (Photon Systems Instruments), using the standard calibration curve provided by the manufacturer. Samples were first treated with 3-(3, 4-dichlorophenyl)-1,1-dimethylurea (DCMU, 50 µM final concentration), an inhibitor of photosystem II in oxygenic phototrophs, so that BChl a fluorescence could be distinguished from Chl a fluorescence (Koblízek et al 2005).…”
Section: Response Parameters -Sampling and Analysismentioning
confidence: 99%
“…Bacteriochlorophyll a (BChl a) concentrations were measured on an FL3500-FT fluorometer (Photon Systems Instruments), using the standard calibration curve provided by the manufacturer. Samples were first treated with 3-(3, 4-dichlorophenyl)-1,1-dimethylurea (DCMU, 50 µM final concentration), an inhibitor of photosystem II in oxygenic phototrophs, so that BChl a fluorescence could be distinguished from Chl a fluorescence (Koblízek et al 2005).Samples for the microscopic enumeration of total bacterial and AAP cells were fixed immediately after collection with 1% glutaraldehyde (final concentration) and kept refrigerated in the dark until filtration. In the lab, samples were filtered onto 0.2 µm poresize black polycarbonate filters and immediately stored at −80°C.…”
mentioning
confidence: 99%